KEPASTIAN HUKUM KEDUDUKAN PERATURAN KOMISI YUDISIAL DALAM HIERARKI PERATURAN PERUNDANG-UNDANGAN DI INDONESIA - Hazmi, Raju Moh; Haskar, Edi; Munandar, Syaiful (Ensiklopedia of Journal, 2025)
Abstract: This study aims to provide an explanation of the legal certainty of the position of the Judicial Commission regulations in the hierarchy of Indonesian legislation. To analyse this legal issue, normative research was used through a conceptual and legislative approach. The data used are secondary data, including primary, secondary, and tertiary legal materials. The analysis of the data will be presented descriptively and qualitatively through content analysis. The results of this research found that, from the perspective of legal certainty theory, the Judicial Commission Regulations do not fall under the category of legislation but rather under the category of internal regulations. The Judicial Commission Regulation, in terms of its substantive content, can be equated with a Presidential Regulation, thus being on par with a Presidential Regulation in the hierarchical structure of legal regulations. It is necessary to improve this by issuing a Judicial Commission Regulation that is no longer considered a legal regulation but rather an internal regulation.Keywords: Legal Certainty; Judicial Commission Regulations; Hierarchy of Legislation; Legislation; Judicial Commission